Low density neutrophils are increased in patients with Behçet's disease but do not explain differences in neutrophil function - Mariam Murad; Liying Low; Matthew Davidson; Philip I. Murray; Saaeha Rauz; Graham R. Wallace (BMC, 2022)
Abstract Background Behçet's disease (BD) is a multisystem autoinflammatory disease characterised by mucosal ulceration, ocular, neural, joint and skin inflammation. The cause of BD is not known but there is a strong genetic association with HLA-B*51, IL10 and IL23R. Neutrophils are a first line of defence against invading pathogens and have been described as activated in patients with BD. Neutrophils can now be separated into different subsets, such as low density (LDN) and normal density (NDN) that have diverse functional roles. We wished to address neutrophil heterogeneity in patients with BD. Methods Peripheral blood neutrophils were obtained from 32 BD patients and 37 healthy aged-matched controls. Percoll isolation was used to isolate all neutrophils, while Ficol-Hypaque was used to obtain LDN and NDN. Phagocytic capacity and production of reactive oxygen species (ROS), and neutrophil extracellular traps (NET) stimulated with phorbol 12-myristate 13-acetate (PMA) and Escherichia coli (E.coli) were assessed in both groups. Results We have demonstrated reduced phagocytic capacity and ROS production but greater NET production by total neutrophils stimulated with PMA or E.coli from BD patients in comparison with healthy controls. Patients with BD had elevated numbers of LDN and lower number of NDN compared with healthy controls. However, both neutrophil subsets showed the same reduced ROS production and phagocytic function as total neutrophils in both groups. Conclusion Our novel findings indicate that the neutrophil population in BD is heterogeneous and the increased number of LDN in combination with greater NET production may contribute to the inflammatory response and pathogenesis.